P385 Tailoring induction treatment for children with Crohn's disease. (21st January 2022) - Cuomo, M; Carobbio, A; Aloi, M; Alvisi, P; Banzato, C; Bosa, L; Bramuzzo, M; Campanozzi, A; Catassi, G; D'Antiga, L; Di Paola, M; Felici, E; et al.
Abstract: Background: Multiple clinical studies in children with Crohn's disease (CD) have demonstrated the high efficacy of nutritional therapy with exclusive enteral nutrition (EEN) to induce remission and even to promote mucosal healing. However, EEN as inductive treatment may be not tolerated or inefficient and we are well aware of the paramount importance of a well conducted induction treatment for paediatric CD with the goal of an individualized induction treatment to improve the prognosis and the quality of life of inflammatory bowel disease (IBD) children. Methods: A retrospective multicentre study including newly diagnosed children with CD treated with EEN as induction therapy was designed. The primary aim of the study was to study predictive factors of non- adherence to treatment. The secondary endpoint were predictive factors of clinical non-remission at the end of induction treatment. Those data together were analysed with the ultimate goal of trying to define an individualized induction treatment for children with CD. Results: 376 CD children from, 14 IBD paediatric referral centres were enrolled in the study. The rate of EEN adherence was, 89 %. Colonic involvement and FC >, 600 μg/g at diagnosis were found associated with a reduced EEN adherence in univariate and multivariate analysis. The remission rate of those who completed induction treatment was, 67%. A multivariate analysis showed that factor determining lower remission rate were age >, 15 years and PCDAI >, 50. With those results we were able to create a decisional algorithm which is provided in figure 1. Conclusion: EEN administered for, 8 weeks is effective for inducing clinical remission. The rate of adherence is high but there is a group of patients (colonic involvement + hight FC) which are at risk of non-adherence and thus may be candidate for alternative dietary induction regimens. Moreover, older patients with moderate to severe active disease (PCDAI>40), are at higher risk of failing clinical remission achievement after EEN and may benefit from an early anti-TNF alpha treatment. Personalized treatment strategies should be proposed weighing the benefits and risks based on each patient's disease location, phenotype and disease activity with the overall aim of obtaining rapid control of inflammation to reduce long-term bowel damage.